Donkey Milk - Papademas, Photis; Aspri, Maria; Malissiova, Eleni; Salimei, E. (My University, 2022)
This article describes the origins and main characteristics of donkey milk i.e., chemical composition, microbiological status as well as the processing methods employed (thermal vs non-thermal), including milk fermentation and innovative products. The functionality/bioactivity of raw milk, fermented milk and the effect of processing are also discussed. Finally clinical studies are presented giving an account on potential positive health benefits to consumers (i.e., infants/children) who suffer from bovine milk allergies.
Keywords: Donkey milk; Non-bovine milk; Lysozyme; Health benefits; Functionality; Processing; Non-thermal; Clinical studies; Infant nutrition; Bioactivity; Antioxidant; Antimicrobial; Immunomodulation; Fermentation